Influence of the Resin Cement Thickness on the Push-Out Bond Strength of Glass Fiber Posts - Marcos,Regina Maria Helen-Cot (2016)
Abstract The objective of the present study was to evaluate the influence of resin cement thickness on the bond strength of prefabricated and customized glass fiber posts after storage in distilled water. Thirty human uniradicular roots were treated endodontically. The roots were divided into 3 groups: THIN (thin cement layer) - post space preparation with #0.5 drill and cementation of #0.5 post; THICK (thick cement layer) - post space preparation with #1 drill and cementation of #0.5 post; and CUSTOM (customized cement layer) - post space preparation with #1 drill and cementation of a customized post (#0.5 glass fiber posts customized with resin composite). All posts were luted with self-adhesive resin cement. The push-out test was carried out after storage for 24 h and 90 days in distilled water at 37 °C. The data were analyzed with three-way ANOVA and Tukey's test (a=0.05). Bond strengths were significantly higher for CUSTOM (9.37 MPa), than for THIN (7.85 MPa) and THICK (7.07 MPa), which were statistically similar. Considering the thirds, the bond strength varied in the sequence: apical (7.13 MPa) < middle (8.22 MPa) = coronal (8.94 MPa). Bond strength for 24 h storage was significantly higher (8.80 MPa) than for 90-day storage (7.40 MPa). It may be concluded that the thickness of resin cement influenced the bond strength of glass fiber posts. The customized posts presented higher bond strength. Storage in water for 90 days affected negatively the values of bond strength, especially for thick cement layers in the apical third.